Cell Phones, Student Rights, and School Safety: Finding the Right Balance - Smale, William T.; Hutcheson, Ryan; Russo, Charles J. (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2021)
Despite the potential instructional benefits of integrating devices such as cell phones into schools and classrooms, research reveals that their improper use can negatively impact student behaviour, learning, and well-being. This paper reviews the literature and litigation on cell phone use in schools due to controversies over cheating, cyberbullying, sexting, and searches of student cell phones. Recent studies suggested that the presence of cell phones and related technologies in classrooms could detract from students’ academic performances while contributing to higher rates of academic dishonesty and cyberbullying. The growing prevalence of cyberbullying is especially concerning because it can have severely negative, even tragic, effects on student mental health and safety. However, given the relatively discreet nature of cell phone use, regulations about their use can be difficult to enforce. After reviewing literature and litigation on the potential risks associated with inappropriate cell phone use in schools, this paper offers suggestions for educators to consider when devising or revising policies balancing students’ individual rights with their safety and well-being before ending with a brief conclusion.